Generation of Oxtr cDNAHA‐Ires‐Cre Mice for Gene Expression in an Oxytocin Receptor Specific Manner. Issue 5 (24th November 2015) - Hidema, Shizu; Fukuda, Tomokazu; Hiraoka, Yuichi; Mizukami, Hiroaki; Hayashi, Ryotaro; Otsuka, Ayano; Suzuki, Shingo; Miyazaki, Shinji; Nishimori, Katsuhiko
ABSTRACT: The neurohypophysial hormone oxytocin (OXT) and its receptor (OXTR) have critical roles in the regulation of pro‐social behaviors, including social recognition, pair bonding, parental behavior, and stress‐related responses. Supporting this hypothesis, a portion of patients suffering from autism spectrum disorder have mutations, such as single nucleotide polymorphisms, or epigenetic modifications in their OXTR gene. We previously reported that OXTR‐deficient mice exhibit pervasive social deficits, indicating the critical role of OXTR in social behaviors. In the present study, we generated Oxtr cDNA HA ‐Ires‐Cre knock‐in mice, expressing both OXTR and Cre recombinase under the control of the endogenous Oxtr promoter. Knock‐in cassette of Oxtr cDNA HA ‐Ires‐Cre consisted of Oxtr cDNA tagged with the hemagglutinin epitope at the 3′ end ( Oxtr cDNA HA ), internal ribosomal entry site (Ires), and Cre . Cre was expressed in the uterus, mammary gland, kidney, and brain of Oxtr cDNA HA ‐Ires‐Cre knock‐in mice. Furthermore, the distribution of Cre in the brain was similar to that observed in Oxtr‐Venus fluorescent protein expressing mice ( Oxtr‐Venus ), another animal model previously generated by our group. Social behavior of Oxtr cDNA HA ‐Ires‐Cre knock‐in mice was similar to that of wild‐type animals. We demonstrated that this construct is expressed in OXTR‐expressing neurons specifically after an infection with the recombinant adeno‐associated virus carrying the flip‐excision switch vector. Using this system, we showed the transport of the wheat‐germ agglutinin tracing molecule from the OXTR‐expressing neurons to the innervated neurons in knock‐in mice. This study might contribute to the monosynaptic analysis of neuronal circuits and to the optogenetic analysis of neurons expressing OXTR. J. Cell. Biochem. 117: 1099–1111, 2016. © 2015 Wiley Periodicals, Inc.